2015
DOI: 10.4103/0250-474x.169030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of formulation factors and compression force on release profile of sustained release metoprolol tablets using compritol®888ato as lipid excipient

Abstract: Metoprolol succinate (MPL), a know cardioselective β-1 adrenergic blocker is widely used to treat cardiovascular diseases like angina pectoris, heart failure, myocardial infarction, hypertension, arrhythmias and others [1][2][3] . MPL is highly water soluble with a half life of 4-6 h which may lead to adverse effects on overdose like severe weakness, fainting, trouble in breathing and very slow heartbeat [4][5] . This resulted in development of sustained release (SR) formulations of MPL like Toprol-XL tablets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Immediate release tablets possessing friable properties may laminate or cap into halves during packaging whiles overly compact tablets may not disintegrate within time to meet the dissolution requirements [ 22 , 26 ]. A minimum crushing force of 3 kg/f is required of tablets formulated as immediate release [ 36 ]. Thus, all the formulated batches will have good resistance to fracture since their crushing strengths were above the minimum value ( Table 4 ) and confirms the suitability of okra pectins as pharmaceutical excipients in the compression of tablets.…”
Section: Resultsmentioning
confidence: 99%
“…Immediate release tablets possessing friable properties may laminate or cap into halves during packaging whiles overly compact tablets may not disintegrate within time to meet the dissolution requirements [ 22 , 26 ]. A minimum crushing force of 3 kg/f is required of tablets formulated as immediate release [ 36 ]. Thus, all the formulated batches will have good resistance to fracture since their crushing strengths were above the minimum value ( Table 4 ) and confirms the suitability of okra pectins as pharmaceutical excipients in the compression of tablets.…”
Section: Resultsmentioning
confidence: 99%
“…A diametric crushing force of 3 kg/F is considered to be the minimum crushing force for an immediate release tablet. All the formulated tablets had crushing forces greater than 3 kg/F, thus being able to withstand fractures optimally ( Table 4 ) [ 35 ]. Binders are added to a tablet formulation to ensure plasticity or elasticity and increase interparticulate bonding strength in the tablet.…”
Section: Resultsmentioning
confidence: 99%
“…Binders are added to a tablet formulation to ensure plasticity or elasticity and increase interparticulate bonding strength in the tablet. This is done to ensure that the tablet remains intact after compression [ 33 – 35 ]. Generally, an increase in binder concentration results in a corresponding increase in tablet hardness due to the increase in interparticulate bonding and film forming properties [ 1 , 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reported sustained-release tablets based on Compritol ® 888 ATO resulting in drug delivery during 12 hours 22 and matrix tablets for sustained release until 20 hours. 24 However, the excipient combination method for the obtention of floating tablets seems to provide DDS with excellent floating properties and satisfactory prolonged release behavior. 25 The combination of hydrophilic polymers and lipophilic excipients has been reported to be a useful strategy for sustained release such as a non-effervescent floating matrix tablet based on cetyl alcohol with HPMC K15M for sustained delivery of MEH during 24 hours 26 and sustained-release pellets based on cellulose and Compritol ® 888 ATO for 24 hours of delivery.…”
Section: Hpmc Effectmentioning
confidence: 99%